CEO Relational Leadership and Product Innovation Performance: The Roles of TMT Behavior and Characteristics - Wang, Yimin; Su, Qianhong; Sun, Wei (Frontiers in Psychology, 2022)
Leadership has been considered as a critical antecedent of product innovation performance. Yet, the relational aspect of leadership has been largely neglected in this area. Drawing upon upper echelons theory and relational leadership literature, this study is intended to explore whether, how and when CEO relational leadership influences product innovation performance. Specifically, we analyze the underlying mechanism of TMT voice behavior and the boundary conditions of TMT educational level and TMT age. Based on multi-source and multi-wave data of 105 Chinese firms, this study finds that CEO relational leadership is positively related to product innovation performance and TMT voice behavior mediates this relationship. Furthermore, the positive relationship between CEO relational leadership and TMT voice behavior is stronger for TMTs with higher educational level and lower age. This study contributes the existing literature by empirically examining the under-investigated research on the relationship p between CEO relational leadership and product innovation performance, and disentangling the underlying mechanism and boundary conditions.